2004
DOI: 10.1007/s10597-004-6124-6
|View full text |Cite
|
Sign up to set email alerts
|

A Pilot Community Intervention for Young Women with Fetal Alcohol Spectrum Disorders

Abstract: Fetal Alcohol Syndrome, a permanent birth defect caused by maternal alcohol use during pregnancy, is a leading preventable cause of mental retardation. Neuropsychological deficits have been well documented, however interventions developed have not been evaluated. We describe a successful 12-month community pilot intervention with 19 young women with Fetal Alcohol Spectrum Disorders (FASD). Improved outcomes (including decreased alcohol and drug use, increased use of contraceptives and medical and mental health… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
67
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(69 citation statements)
references
References 20 publications
2
67
0
Order By: Relevance
“…In the Parent and Child Assistance Program [PCAP; Grant et al, 2002], paraprofessionals worked with mothers with alcohol and substance use problems to connect them with appropriate services, taught them to access services for both themselves and their children, and facilitated their ability to provide a safe caregiving environment for their children. A subsequent adaptation of PCAP for young women with FASDs indicated that participation in PCAP resulted in a reduced percentage of women with unmet mental health and medical needs, and an increased percentage with stable housing, as well as decreases in alcohol and substance use and increases in the use of reliable contraception, outcomes that are likely to contribute to the prevention of additional alcohol-exposed pregnancies [Grant et al 2004]. Such approaches are also critical in the light of the multitude of other significant postnatal risk factors that may cooccur with prenatal alcohol exposure.…”
Section: Recommendations and Future Directionsmentioning
confidence: 99%
“…In the Parent and Child Assistance Program [PCAP; Grant et al, 2002], paraprofessionals worked with mothers with alcohol and substance use problems to connect them with appropriate services, taught them to access services for both themselves and their children, and facilitated their ability to provide a safe caregiving environment for their children. A subsequent adaptation of PCAP for young women with FASDs indicated that participation in PCAP resulted in a reduced percentage of women with unmet mental health and medical needs, and an increased percentage with stable housing, as well as decreases in alcohol and substance use and increases in the use of reliable contraception, outcomes that are likely to contribute to the prevention of additional alcohol-exposed pregnancies [Grant et al 2004]. Such approaches are also critical in the light of the multitude of other significant postnatal risk factors that may cooccur with prenatal alcohol exposure.…”
Section: Recommendations and Future Directionsmentioning
confidence: 99%
“…Improvements can include changes in substance use, mental health symptoms, perinatal or birth outcomes, employment, self-reported health status, and HIV risk reduction [Ashley et al, 2003;Brady and Ashley, 2005]. There has also been success with intensive case management approaches for women at highest risk for having a child with a FASD and women who themselves have a FASD [Grant et al, 1996[Grant et al, , 2004, although more research in this area is warranted. The Task Force recognized this and also stressed the importance of assuring access to substance abuse treatment services and the availability of appropriate substance abuse treatment options for women of childbearing age.…”
Section: Selective and Indicated Prevention Strategiesmentioning
confidence: 99%
“…This one year, pre-and post-treatment outcome study by Grant, Huggins, Connor, Pedersen, Whitney and Streissguth (2004) explored the efficacy of a community intervention model. The model involved targeted education and collaboration with key service providers, in combination with intensive paraprofessional advocacy case management.…”
Section: Community Intervention For Young Women With Fasd -Education mentioning
confidence: 99%